Conditions of embryo culture from days 5 to 7 of development alter the DNA methylome of the bovine fetus at day 86 of gestation - Li, Yahan (J Assist Reprod Genet, 2019)
PURPOSE: We tested whether in vitro production (IVP) causes changes in DNA methylation in fetal liver and skeletal muscle and if exposure of cultured embryos to colony-stimulating factor 2 (CSF2) alters DNA methylation. METHODS: Female fetuses were produced by artificial insemination or transfer of an IVP embryo. Embryos were treated from days 5 to 7 after fertilization with CSF2 or vehicle. DNA methylation in fetal liver and skeletal muscle was determined by post-bisulfite adaptor tagging-based sequencing. The degree of DNA methylation for CpG sites in 50-bp windows of the promoter region 500 bp upstream of the transcriptional start site was compared between treatments. RESULTS: For liver, there were 12 genes (6% of those analyzed) in which DNA methylation was affected by treatment, with one 50-bp window per gene affected by treatment. For muscle, the degree of DNA methylation was affected by treatment for 32 windows (19% of the total windows analyzed) representing 28 distinct genes (23% of analyzed genes). For 19 of the 28 genes in muscle, the greatest deviation in DNA methylation was for the CSF2 group. CONCLUSION: Results are consistent with alterations in the methylome being one of the mechanisms by which IVP can result in altered fetal development and postnatal function in the resultant offspring. In addition, results indicate that maternally derived cell-signaling molecules can regulate the pattern of DNA methylation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-019-01652-1) contains supplementary material, which is available to authorized users.